Infraestrutura e serviços de saúde: proposta de um plano de manutenção preventiva para o sistema hidrossanitário do Departamento de Oftalmologia e Ciências Visuais da Universidade Federal de São Paulo - Vieira, William Silva [UNIFESP] (2021)
The hospital building is integrated by a set of complex services dependent on sophisticated facilities operating around the clock and management and articulated technologies for efficient and safe care. The hydrosanitary facilities in health services are susceptible to higher wearing due to the nature of the activities and a diversified and intense flow of users, demanding attention and control of biological risks for the environment and for professionals. The proper functioning and the maintenance focus on the durability, the system and people safety and the service efficiency.The infrastructure needs upgrades, partially or totally, or innovations, processes with careful engineering and logistics approaches that must be foreseen during the building conception. In environments like the Department of Ophthalmology and Visual Sciences of the São Paulo Federal University, the object of this study, teaching, research and assistance activities cause hundreds of people to go and come in the building daily, including teachers, students, diverse professionals, collaborators and patients. Objective: The project comes up with a preventive building maintenance plan for the hydrosanitary system of the Department of Ophthalmology and Visual Sciences, updating the methodology and procedures of the current management to ensure the proper functioning of medical and hospital services, minimizing interference in services and discomfort for users during interventions. Methods: The maintenance system of the civil construction, nonstructural components, installations and water distribution and wastewater drainage equipment of the Department's hydrosanitary system were evaluated based on onsite and documentary surveys at the Engineering and Infrastructure Department of the São Paulo campus and through consultings with the team of professionals of the sector. A graphic table was organized and photographic records were made. The bibliographic review covered the themes of infrastructure maintenance and management, regulations and building maintenance planning. The analysis were based on extensions of civil engineering, detailed in the recent months by the hospital context, facing the challenges of Covid-19, putting in check the organization of health services and the safety of users. Results: Based on the Service Orders of the Maintenance Department of the Hospital São Paulo and photographic records, the prevailing demands for hydrosanitary maintenance in the period studied were demonstrated and after this survey, an inspection check list, a conformity control check list, and an action plan for the corrective maintenance of the anomalies found were prepared. Conclusions: The planning guarantees the prioritization of maintenance and the planing of resources for contructions, following specific protocols for each situation. The data indicated the need for deepening the diagnosis in the Department of Ophthalmology and Visual Sciences, essential for preventive actions, the effectiveness of the planning and maintenance process, and that the periodicity of maintenance and the identification of the source of the problems must be subject to continuous observation to guarantee the proper functioning of the system and the plan functionality and support the security of the facilities and operations and the health of users.